Photorelease of amino acid neurotransmitters from pyrenylmethyl ester conjugates - Fernandes, Maria J. G. (2007)
The linkage of model neurotransmitter L-amino acids, such as glycine, alanine, beta-alanine, glutamic acid and gamma-aminobutyric acid, to a pyrenylmethyl group as the fluorescent moiety through an ester bond at their carboxylic functions at the main and side chains (in the case of glutamic acid) was investigated. The behaviour of the resulting fluorescent conjugates towards photocleavage was studied in different cleavage conditions, namely the wavelength of irradiation and the use of different solvents, in a photochemical reactor equipped with lamps of 254, 300, 350 and 419 nm, followed by HPLC/UV monitoring. (C) 2007 Elsevier Ltd. All rights reserved.